Au130−xAgx Nanoclusters with Non‐Metallicity: A Drum of Silver‐Rich Sites Enclosed in a Marks‐Decahedral Cage of Gold‐Rich Sites. (8th November 2019) - Higaki, Tatsuya; Liu, Chong; Morris, David J.; He, Guiying; Luo, Tian‐Yi; Sfeir, Matthew Y.; Zhang, Peng; Rosi, Nathaniel L.; Jin, Rongchao
Abstract: The synthesis and structure of atomically precise Au130− x Ag x (average x= 98) alloy nanoclusters protected by 55 ligands of 4‐ tert ‐butylbenzenethiolate are reported. This large alloy structure has a decahedral M54 (M=Au/Ag) core. The Au atoms are localized in the truncated Marks decahedron. In the core, a drum of Ag‐rich sites is found, which is enclosed by a Marks decahedral cage of Au‐rich sites. The surface is exclusively Ag−SR; X‐ray absorption fine structure analysis supports the absence of Au−S bonds. The optical absorption spectrum shows a strong peak at 523 nm, seemingly a plasmon peak, but fs spectroscopic analysis indicates its non‐plasmon nature. The non‐metallicity of the Au130− x Ag x nanocluster has set up a benchmark to study the transition to metallic state in the size evolution of bimetallic nanoclusters. The localized Au/Ag binary architecture in such a large alloy nanocluster provides atomic‐level insights into the Au−Ag bonds in bimetallic nanoclusters. Abstract : Reich an Gold und Silber : Au130− x Ag x (TBBT)55 wurde synthetisiert und strukturell charakterisiert. Der große Dimetall‐Nanocluster zeigt eine Lokalisation von Au‐Atomen unter Bildung eines Marks‐Dekaeders; fs‐Spektroskopie zufolge ist dieser Nanocluster nichtmetallisch, und eine XAFS‐Analyse offenbarte einen Ladungstransfer innerhalb des Kerns. Es wurden Einblicke in die Strukturregeln, Legierungsmuster und nichtmetallischen Eigenschaften erhalten.